Kharismata dan Pertumbuhan Gereja: Analisis Teologis dan Praktis: Charismata and Church Growth: A Theological and Practical Analysis - Suria, Isak (Sekolah Tinggi Teologi Satyabhakti, East Java, 2025)
Abstract This study examines the role of charisma in church growth from a theological and practical perspective with a qualitative approach. The research methods used include literature studies and comparative analysis of churches that emphasize using spiritual gifts in their ministry. Data was obtained from primary sources such as biblical texts, theological commentaries, interviews with church leaders, and secondary sources from scientific journals and previous research. The results showed that churches adopting charismatic practices, such as healing, prophecy, and speaking in tongues, experienced faster congregational growth than more structured churches. However, other factors such as visionary leadership, innovative evangelistic strategies, and the use of digital technology have also significantly impacted church expansion. Additionally, the study identifies challenges charismatic churches face, including theological instability and a lack of a deep understanding of biblical teachings. The discussion of this research highlights the importance of balancing charisma and a more holistic church growth strategy. Churches can achieve stable and sustainable growth by understanding the interplay between charisma and other factors, such as leadership and evangelistic strategies.